2021
DOI: 10.1177/20587384211005645
|View full text |Cite
|
Sign up to set email alerts
|

Thymulin and peroxiredoxin 6 have protective effects against streptozotocin-induced type 1 diabetes in mice

Abstract: Protective effects of peroxiredoxin 6 (PRDX6) in RIN-m5F β-cells and of thymulin in mice with alloxan-induced diabetes were recently reported. The present work was aimed at studying the efficiency of thymulin and PRDX6 in a type 1 diabetes mellitus model induced by streptozotocin in mice. Effects of prolonged treatment with PRDX6 or thymic peptide thymulin on diabetes development were evaluated. We assessed the effects of the drugs on the physiological status of diabetic mice by measuring blood glucose, body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our studies with streptozotocin induced murine T1D model also revealed the Prdx6 associated protective effect [82]. Owing to the clinical application of STZ as a chemotherapeutic agent details regarding its mode of action are known [83].…”
Section: Protective Effects Of Peroxiredoxin 6 In Various Models Of Type 1 Diabetesmentioning
confidence: 63%
See 2 more Smart Citations
“…Our studies with streptozotocin induced murine T1D model also revealed the Prdx6 associated protective effect [82]. Owing to the clinical application of STZ as a chemotherapeutic agent details regarding its mode of action are known [83].…”
Section: Protective Effects Of Peroxiredoxin 6 In Various Models Of Type 1 Diabetesmentioning
confidence: 63%
“…It may be assumed that Hsp90α could serve as one of the T1D markers. Abrupt upregulation of the expression of Hsp90α was observed in the RIN m5F beta cells in in vitro settings [92], as well as in immune cells from the mice with STZ induced T1D [82]. In the process Prdx6 fully normalized the level of Hsp90α in immune and beta cells.…”
Section: Protective Effects Of Peroxiredoxin 6 In Various Models Of Type 1 Diabetesmentioning
confidence: 91%
See 1 more Smart Citation
“…It increases the expression of SLC7A11 and GPX4 and inhibits ferroptosis. Interestingly, PRDX6 reduced the activation of plasma NF- κ B and TNF- α levels in diabetic mice [ 31 ]. These results strongly suggest that PRDX6 can improve renal function by inhibiting ferroptosis, which may be closely related to improving inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the insulin-stimulating activity of Prx6 in vitro was detected both when RIN-m5F β-cells were cultivated under normal conditions and under stressful conditions, inducing cell death [99]. In an alloxan-or streptozotocin-induced mouse model of diabetes, intravenous administration of recombinant Prdx6 prevented hyperglycemia, reduced mortality, restored the plasma cytokine profile, and reduced β-cell destruction in the islets of Langerhans in the mouse pancreas [100][101][102].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%